MODUL INTERAKTIF EFEK FOTOLISTRIK BERBASIS LCDS UNTUK MENSTIMULUS KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SAINS - Ani Latifatun Naj'iyah; Agus Suyatna; Abdurrahman Abdurrahman (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this research are to knowing the differences of critical thinking skills using interactive module photoelectric effects with printed module, describe the improvement of students' critical thinking skills after the interactive module is applied, describe science process skills in students who use interactive module of photoelectric effects, and knowing student responses to the use interactive module of photoelectric effects. The study was conducted in Natar 1 Public High School, in the even semester 2018/2019 academic year with research design nonequivalent control group design.The research instrument used was a questionnaire (questionnaire), Student Worksheet (LKPD) along with observation sheets and test questions. Data collection techniques were carried out by test techniques, questionnaires and LKPD contents. The data analysis technique of critical thinking ability is done by normality test, homogeneity test and N-gain. The data analysis technique of science process skills is done by calculating the average grade of the class then adjusted to the index classification table of science processes. Hypothesis testing is done by Paired Sample T Test and Independent Sample T Test. The results of the study show that (1) the application of the photoelectric effect interactive module is able to improve students' critical thinking skills, this is seen from the N-gain value and paired sample t test results, 2) there are significant differences in critical thinking skills between students who use interactive modules with printed modules, this is seen from the differences in the n-gain values of both classes and the results of the independent sample t test, (3) the value of students' science process skills is 82.6 with a high category, and (4) students gave a positive response to the utilization of the photoelectric effect interactive module.